Cultural Interference on the Use of English Second-Person Pronoun by Javanese Students - Retno Setya Budiasningrum (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2020)
Learning a language is not only about grammar and vocabulary but also about culture. Understanding culture allows language learners to give the right meaning to each word learned. English has a different culture from Indonesian. This study described the students' problems in using the second - person pronoun "you" in English, by looking at the term of social and cultural variables that are given in written form test. It involved the 40 students in ninth grade of SMP Sriwedari Malang, 80 students of SMA 3 Surabaya and 80 students of SMA 17 Surabaya. To examine the appropriateness of using second - person pronoun “you” the following steps were taken; analyzing the pronominals used by the samples, tabulating the pronominals used and the addressee interactions and the last step was calculating the percentage of pronominals used. The obtaining answer from the test explained that students’ answers were various. There were “you” as kinship term and others form were found to take the place of “you”. Kinship terms are “grandfather”, “aunt”, “uncle”, “mother”, “brother” and “father”. Other forms include “he”, “Herlina” (name), “Herman and “Levina” (names). It was found that 25.3% students used the correct form “you”, 69.05% students used   kinship terms   and 5.65% students used other forms. The analysis showed that there are some errors made by Javanese students in using the second - person pronoun “you” in English. It indicated that they still have culture interference in using second - person pronoun “you” in English.